Diagnostic consideration in cases of pulmonary embolism mimicking acute coronary syndrome : Is electrocardiography a friend or a foe? - Chew, Keng Sheng; Chui, Elise King Wong; Nariman, Singmamae; A., Aaron K. Lai; Seri Diana, Mahmud Affandi (Malaysian Society of Applied Biology, 2018)
Objectives: As the clinical presentations of pulmonary embolism (PE) closely mimic that of acute coronary syndrome (ACS), the purpose of this brief report is to study the effect of adding an electrocardiography tracing (ECG) suggestive of ACS on the diagnostic consideration of PE with chest pain presentation. Methods: Twenty final year medical students and 31 house officers randomized to one of two cases of PE patients presented with clinical and ECG suggestive of ACS. Each of these two cases was divided further into either with ECG tracing attached or without. Results: More participants without ECG attached had considered PE as a differential diagnosis vs those provided with ECG (8 out of 25, 32% vs. 6 out of 26, 23% respectively, p=0.48). Specifically for the first case, the consideration of PE as a differential diagnosis was significantly higher when ECG was not attached compared to when it was attached (4 out of 13 or 30.8% vs. 0 out of 14, p = 0.04). Conclusion: In cases where the clinical signs and symptoms mimic that of an ACS, performing an ECG with features mimicking ACS may not only be unhelpful, but may paradoxically deter consideration of PE.